2020
DOI: 10.21203/rs.3.rs-26039/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prediction and identification of immune genes related to the prognosis of patients with colon adenocarcinoma and its mechanisms

Abstract: Abstract Background Colon adenocarcinoma(COAD) is a type of gastrointestinal tumor with a high degree of malignancy, and its immunotherapy method has been stagnant. Recently, with the development of network databases and the development of bioinformatics tools, we can analyze the data in the current database to find out which genes may be the target of immunotherapy for COAD. Methods We use various codes and packages in R language to analyze the downloaded data, const… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The results of this research highlight that myeloid dendritic cells mainly results from lymphatic metastasis of COAD. Myeloid dendritic cells can eliminate inflammation by inhibiting the activity of macrophages, but their regulatory mechanism in colon cancer requires further study [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this research highlight that myeloid dendritic cells mainly results from lymphatic metastasis of COAD. Myeloid dendritic cells can eliminate inflammation by inhibiting the activity of macrophages, but their regulatory mechanism in colon cancer requires further study [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Black module has relatively high Z summary score and low median rank, indicating high preservation. In the current study, all the four gene modules were considered to be conserved and selected for further 2020:08:51875:2:1:NEW 19 Nov 2020) Manuscript to be reviewed in colon adenocarcinoma (Chen et al 2020;Li et al 2020;Miao et al 2020;Sun et al 2020), and the role of INHBA in gastric cancer has been widely reported also. INHBA was highly expressed (Kaneda et al 2011;Seeruttun et al 2019;Zhang et al 2010) and aberrantly methylated (Zhang et al 2019) in gastric tumor samples, and high INHBA expression was associated with significantly poorer 5-year survival than low expression group (Katayama et al 2017;Wang et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, KRAS proto-oncogene and TP53 tumor suppressor gene are related to the development and prognosis of colon cancer [ 5 , 6 ]. Likewise, INHBA plays an immunomodulatory role in colon cancer [ 7 ], and BRIP1 is related to the susceptibility of colon cancer [ 8 ]. At present, although radical resection combined with chemotherapy can improve the survival rate of colon cancer, the treatment results are still unsatisfactory [ 9 ].…”
Section: Introductionmentioning
confidence: 99%